Cycloadditions as a Sweet Route to ‘Double C-Glycosylation’ - Kevin P. P. Mahoney; Rosemary Lynch; Rhea T. Bown; Sunil V. Sharma; Piyasiri Chueakwon; G. Richard Stephenson; David B. Cordes; Alexandra M. Z. Slawin; Rebecca J. M. Goss (Biomolecules)
Pharmaceuticals, such as the antibiotic erythromycin, and sodium-dependent glucose transporter (SGLT1 & SGTL2) inhibitors such as Bexagliflozin (diabetes) and Sotagliflozin (heart disease), are often sugar-decorated (glycosylated). Glycosylation is a key component of the binding motif in SGLT inhibitors and, in natural products, glycosylation often confers improved bioactivity and bioavailability. Whilst a single C-glycoside link between a sugar moiety and its aglycone core is a common feature in natural products isolated to date, only a small number, including the antibiotics granaticin and sarubicin, are covalently bonded twice to a single sugar moiety. The way in which this “double C-glycosylation” is naturally mediated is not yet known, yet has been speculated on. Here, we report the exploration and development of a potentially biomimetic procedure that utilises intermolecular cycloaddition chemistry to access new “double C-glycosylated” products and enables the creation of bridged polycyclic ethers from a common maltol-derived oxidopyrylium salt precursor.